2008
DOI: 10.1029/2008gl035418
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical production of hydroxyl radical and hydroperoxides in water extracts of nascent marine aerosols produced by bursting bubbles from Sargasso seawater

Abstract: [1] Marine aerosols produced by bursting bubbles at the ocean surface are highly enriched in organic matter (OM) relative to seawater. The importance of this OM in the photochemical evolution of marine aerosols, particularly as a source of reactive oxidants, is unknown but likely significant. To investigate oxidant production, nascent aerosols were generated by bubbling zero air through flowing Sargasso seawater and photochemical production of OH radical and hydroperoxide were quantified in aqueous aerosol ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 22 publications
0
52
0
Order By: Relevance
“…45,46 Our experimental conditions were also not designed to capture the chemistry resultant from secondary reaction products due to aging of SSA during ambient outdoor exposure, including inorganic acids (primarily HNO 3 , H 2 SO 4 , and HCl), 47 oxalic acid 48 and reactive transient species resultant from photochemistry (e.g., H 2 O 2 , peroxy radicals, and halogen radicals). 49,50 This is especially important in the case of finer aerosol which can be transported tens to hundreds of km inland, 51 and due to their longer atmospheric lifetime (hours to days), can exhibit drastically altered chemistry. 52 Although some of these complexities have been demonstrated to have significant impact on the atmospheric corrosion behavior of other alloy systems, 51,[53][54][55][56] their effect on the hygroscopic behavior of SSA as it relates to the corrosion response of mild steel remains a topic for future work.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 Our experimental conditions were also not designed to capture the chemistry resultant from secondary reaction products due to aging of SSA during ambient outdoor exposure, including inorganic acids (primarily HNO 3 , H 2 SO 4 , and HCl), 47 oxalic acid 48 and reactive transient species resultant from photochemistry (e.g., H 2 O 2 , peroxy radicals, and halogen radicals). 49,50 This is especially important in the case of finer aerosol which can be transported tens to hundreds of km inland, 51 and due to their longer atmospheric lifetime (hours to days), can exhibit drastically altered chemistry. 52 Although some of these complexities have been demonstrated to have significant impact on the atmospheric corrosion behavior of other alloy systems, 51,[53][54][55][56] their effect on the hygroscopic behavior of SSA as it relates to the corrosion response of mild steel remains a topic for future work.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Zhou et al (2008) found evidence that primary organic matter emitted within sea spray is a dominant sink for the OH radical, with its consequent degradation and the likely production of a series of low-molecular weight organic compounds. These can partition into the gas phase and contribute to SOA formation.…”
Section: Secondary Organic Marine Aerosolmentioning
confidence: 99%
“…The organic fraction of SSA particles will affect their size as a function of RH (Ming and Russell, 2001) and therefore their scattering potential (Randles et al, 2004), their ability to act as CCN (Moore et al, 2008) and also their role in atmospheric chemistry (Zhou et al, 2008). The purpose of this study was to investigate and quantify the organic fraction of bubble-chamber-generated accumulation mode SSA using an original, independent and on-line method: the Volatility Hygroscopicity-Tandem Differential Mobility Analyser (VH-TDMA).…”
Section: Introductionmentioning
confidence: 99%